Небывалое бывает: повести и рассказы - Алексеев Сергей Петрович (1982)
Экземпляры: ф.16 (1982) / Инвентарный номер: 3451 / Цена: 1.20 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 47 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6